Rationale and design of the Medication adherence Improvement Support App For Engagement—Blood Pressure (MedISAFE-BP) trial - Morawski, Kyle; Ghazinouri, Roya; Krumme, Alexis; McDonough, Julianne; Durfee, Erin; Oley, Leslie; Mohta, Namita; Juusola, Jessie; Choudhry, Niteesh K. (The American heart journal, 2017)
Hypertension is a major contributor to the health and economic burden imposed by stroke, heart disease, and renal insufficiency. Antihypertensives can prevent many of the harmful effects of elevated blood pressure, but medication nonadherence is a known barrier to the effectiveness of these treatments. Smartphone-based applications that remind patients to take their medications, provide education, and allow for social interactions between individuals with similar health concerns have been widely advocated as a strategy to improve adherence but have not been subject to rigorous testing. The MedISAFE-BP study is a prospective, randomized control trial designed to evaluate the impact on blood pressure and medication adherence of an mhealth application (Medisafe). Four hundred thirteen patients with uncontrolled hypertension have been enrolled and randomized in a 1:1 fashion to usual care or to the use of the Medisafe mhealth platform. Patients will be followed up for 12 weeks and the trial's co-primary outcomes will be change in systolic blood pressure and self-reported medication adherence. The MedISAFE-BP trial is the first study to rigorously evaluate an mhealth application's effect on blood pressure and medication adherence. The results will inform the potential effectiveness of this simple system in improving cardiovascular disease risk factors and clinical outcomes.